Development of a Sensitive Bioanalytical Method for the Quantification of Lacosamide in Rat Plasma. Application to Preclinical Pharmacokinetics Studies in Rats - Shah, S.; Vasantharaju, S. G.; Arumugam, K.; Muddukrishna, B. S.; Desai, N. (Arzneimittelforschung, 2012)
A sensitive and selective high performance liquid chromatographic (HPLC) method was developed and validated for quantification of lacosamide in rat plasma. A liquid-liquid extraction procedure was optimized to extract lacosamide from rat plasma. Chromatographic separation was accomplished using a reversed phase C18 Hichrom (250×4.6 mm, 5 µm) column with the mobile phase consisting of acetonitrile-phosphate buffer (pH 3.2±0.1; 20 mM) (21:79, v/v) at a flow rate of 1 mL/min. Both intra- and inter day assay precision and accuracy were lower than 15% CV. The lower limit of quantitation was 25 ng/mL for lacosamide and the response was linear in a concentration range from 25 to 10 000 ng/mL. The developed method was successfully used for the preclinical pharmacokinetic study of lacosamide in rats.
Keywords: lacosamide; HPLC method; rat plasma; pharmacokinetics; validation